A digital learning media based augmented reality Animalia material to increase understanding of concepts and interest in learning for Class X high school students - Pambudi, Sholeh; Subiantoro, Agung Wijaya (JURNAL BIOEDUKATIKA, 2022)
This research aims to determine the feasibility and effectiveness of digital learning media with augmented reality, developed to increase students' understanding of concepts and interest in learning. This research is Research and development using the Design and Development Research (D&DR) model, which consists of four stages, namely analysis, planning, production, and evaluation. This research was conducted at SMAN 1 Prambanan, Sleman. The test subjects were class XI MIPA students to get student response data, while the research sample was class X students to get data on the effectiveness of media use. Data collection techniques include questionnaires to obtain product feasibility data, while multiple-choice tests and learning interest questionnaires are used to obtain data on the effectiveness of media use. The results of the media suitability questionnaire were analyzed descriptively. In contrast, the data results for the media effectiveness test were analyzed using the Mann-Whitney Test and Independent Sample T-test. The research results showed that the development of augmented reality media on Animalia material was declared feasible with scores of 95.3% (media expert), 96.5% (material expert), 93.2% (Biology teacher), and 81.2% (student response). Learning Animalia material using AR media is less effective than learning without AR media in increasing students' understanding of concepts and interest in learning. However, there is a tendency to increase student understanding of concepts and greater interest in learning when learning with AR media.